Peran Digital Retouching Pada Iklan Dalam Peningkatan Brand Image dan Brand Attitude Suatu Brand - Michelle Sinatra; Christian Anggrianto (Universitas Ciputra Surabaya, 2019)
This study aims to determine the role of digital retouching in advertising in improving the brand image and brand attitude of a brand. To find out, research will be conducted based on primary data in the form of interviews with expert users and extreme users. Secondary data retrieval is also held by collecting data from various books, journals and websites that contain advertising theory, the influence of brand image and brand attitude on brands, consumer behavior, marketing communication through visual design and psychology of advertising. The results of the study concluded that digital retouching can increase the brand image and brand attitude of a brand.